Within-scale and cross-scale interaction effects of temperature and human socioeconomic conditions on avian abundance - Anand Chaudhary (Resilience Alliance, 2020)
The interactive effects of climate and human socioeconomic factors on biodiversity in the Anthropocene may be studied most effectively from a social-ecological perspective. Climate can affect avian abundance, and socioeconomics may affect the human propensity to contribute to conservation. Yet, little is known about how these two factors interact to affect species. We assessed the relative influence of within-scale (landscape) and cross-scale (region-landscape) interaction effects of breeding-season temperature and four socioeconomic variables (percent female, percent college educated, median age, and median income) on the relative abundance of eight forest bird species in the Eastern Temperate Forest Ecoregion of North America. We used negative binomial regression to model relative abundance over three years. Akaike's Information Criterion for small sample sizes (AICc) was used to rank a set of nine a priori models for each combination of species and socioeconomic variable. Of the 32 best-supported models, seven included informative within-scale interactions and three additional models included informative cross-scale interactions, indicating that the relationships between species' relative abundance and socioeconomic variables varied for different levels of temperature. Our results suggest that interactions were generally less influential than were climate, socioeconomic, and habitat variables. Distinct responses to interactions were not evident between habitat groups or between wintering groups. Interactions between human socioeconomic variables and breeding-season temperature at different spatial scales can affect forest bird abundance in species-specific ways. Ignoring the effects of interactions on broad-scale patterns of avian abundance may result in misleading interpretations about additive effects and, consequently, ineffective use of limited conservation resources.